Examining the Relationship Between Learning Needs and Quality of Life in Patients with Stoma - Yurdagül, Gülistan; Dusak, İsmail (The European Research Journal, 2026)
Objectives: To examine the relationship between the learning needs and quality of life of patients with a stoma. Methods: This descriptive and correlational study was conducted with stoma patients receiving care in the surgical and oncology units of a training and research hospital between September 25, 2023 and April 25, 2024. The study was completed with 208 patients who volunteered to participate and met the inclusion criteria. Data were collected through face-to-face interviews using the Patient Information Form, Patient Learning Needs Scale, and Stoma Quality of Life Scale. Data were analyzed with SPSS 23 using Kruskal–Wallis, ANOVA, Student’s t-test and Mann–Whitney U test. A significance level of P<0.05 was accepted. Results: There was no significant relationship between the learning needs and quality of life of stoma patients (P>0.05). However, patients with rectal cancer had significantly higher scores on the body image/sexuality subscale (t = -2.902, P=0.004) and total quality of life (t = -2.264, P=0.025) compared to those with colon cancer. Conclusions: The higher body image/sexuality and quality of life scores among patients with rectal cancer suggest that their care needs may be more related to social acceptance rather than purely physiological processes.